Pu Sapi dan Lembu Agra: Kajian Antroponimi Berdasarkan Isi Prasasti Jawa Kuno (Abad ke-9–16 M) - Sasongko, Chacuk Tri; Susanti, Ninie (UI Scholars Hub, 2021)
Javanese literary works, especially the Panji tales, often feature human characters with animal names, such as Kuda Narawangsa, Kebo Kanigara, and Kidangwalangka. This naming phenomenon can also be found in old Javanese inscriptions. Recent studies generally concluded that such naming tradition occurred during the Kadiri-Majapahit era, and this was closely related to the banner of the army and the identity of makasirkasir. This study aims to reveal the motivation behind the naming tradition and the relationship between personal name, social status, and occupation of the person so named throughout the ancient Javanese era. This study uses Nyström’s onomastical approach, especially the concept of anthroponomics, namely the presuppositional meanings of proper names consisting of categorial, associative, and emotive meanings. This research utilized archaeological methods which involved data collection, data processing, and interpretation. Results show that this naming phenomenon was generally motivated by people’s appreciation of certain animals that had a special place and played an important role in the ancient Javanese society and culture. The correlation between the names and the characters’ social status and occupation has been found to be influenced by the sociocultural development during the Ancient Mataram and Kadiri-Majapahit periods.